Quality indicators of integrated care for patients with head and neck cancer. (20th September 2016) - van Overveld, L.F.J.; Braspenning, J.C.C.; Hermens, R.P.M.G.
Abstract : Objectives: Oncological care is very complex, and delivery of integrated care with optimal alignment and collaboration of several disciplines is crucial. To monitor and effectively improve high‐quality integrated oncological care, a dashboard of valid and reliable quality indicators (QIs) is indispensable. The aim was to develop multidisciplinary QIs to measure quality of integrated oncological care, specifically for head and neck cancer (HNC) patients. Design: The RAND‐modified Delphi method was used to decide on the outcome, process and structure QIs form three different perspectives. In addition, case‐mix factors were determined. Setting: Integrated HNC in the Netherlands. Participants: Head and neck cancer patients, chairmen of both patient organisations and medical specialists and allied health professionals involved in HNC care in the Netherlands. Main outcome measures: Outcome, process and structure indicators. Results: Outcome indicators were assigned to healthcare status, tumour recurrence, complications, quality of life and patient experiences. The process indicators focused on the (allied health) care aspects during the diagnostic, treatment and follow‐up phases, for example regarding waiting times, multidisciplinary team meetings and screening for the need of allied health care. Conclusions: This is the first set of multidisciplinary QIs for HNC care, to assess quality of integrated care agreed by patients and professionals. This set can be used to build other oncological quality dashboards for integrated care.